Political analysis of civil protection as a security function of EU member countries - Бірюков, Д. С.; Лещенко, О. Я. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2016)
Political aspects of civil protection as a security function of modern state are investigated on the case of EU Member Countries. We use multicomponent approach for the analysis, which investigates the following issues: extents of the politization of certain security function (its inclusion into strategic, doctrinal and political agenda frameworks), the socio-economic influence, and the implementation of security partnership (involvement of all stakeholders - government, society, and business), decentralization (devolution of powers from central to local government), regional cooperation and integration.